Weight loss did not modify macronutrient specific response of hormones and satiety in overweight and obese people without metabolic disease – results from a clinical trial. Issue 4 (April 2022) - Li, Linna; Decker, Anne-Marie; Stobäus, Nicole; Beer, Finja; Grittner, Ulrike; Spranger, Joachim; Mai, Knut
Summary: Background & aims: Sustained weight loss is highly desirable in obesity. Although the role of incretins in the regulation of body weight is well known, macronutrient specific incretin response and the effects of weight loss on this response have not been investigated before. We aimed to examine GLP-1, GIP, ghrelin, insulin, and satiety response to meals with different macronutrient composition in overweight and obese subjects before and after weight loss. Methods: 32 overweight and obese participants underwent meal tests before and after weight loss intervention. Test meals were designed to be either carbohydrate (CHO), fat (FAT), or protein (PRO) enriched to test macronutrient specific response. Macronutrient specific response of GLP-1, GIP, and ghrelin before and after weight loss were the primary outcome measures. Response of insulin and satiety were predefined secondary endpoints. Results: There were macronutrient specific response patterns of GLP-1 (PRO>FAT=CHO), GIP (CHO=FAT>PRO), and insulin (CHO>PRO=FAT). Postprandial decline of ghrelin did not differ between the test meals. Hunger, desire to eat, and prospective food consumption were highest after CHO intake (CHO>PRO=FAT) at baseline. After weight loss, fasting and postprandial GLP-1 and insulin were reduced while concomitant ghrelin levels were increased. However, the macronutrient specific hormonal response pattern did not change after weight loss. While weight loss increased hunger and desire to eat, the macronutrient specific differences were lost after weight reduction. Higher weight loss was associated with a stronger decline of PRO induced GLP-1 response (ρ = 0.45, p = 0.024, n = 27). Conclusions: Both hormones and satiety showed a macronutrient specific response in overweight/obese participants with a possibly favorable role of protein. However, weight loss may cause a partial disruption of this hormone-satiety-connection as macronutrient specific response pattern of satiety scores representing impulse control in particular but not incretins disappeared. Trial registration: NCT02649907. https://clinicaltrials.gov/ct2/show/NCT02649907